Mercury Removal From Produced Water Using Subcritical Water Assisted 1-Etyl-3- Methylimidazolium Chloride Ionic Liquid (Journal of Chemical Engineering, 2017)
Production of produced water from oil and gas industries are increasing day by day for enhancement of oil recovery. Insoluble mercury such as mercury sulfide and oxide, and dissolved mercury such as organomercury, ionic mercury and elementary mercury are present in produced water along with the other impurities. Mercury is not only hazardous to human health and the environment but could also attack process equipment components that have mercury reactive materials, leading to potential catastrophic failure to the plant. So, removing mercury from produced water is now a pressing issue for the environmental point of view. A lot of mercury separation techniques such as adsorption, precipitation etc. have been developed all over the world. But the traditional mercury removal processes are not suitable to remove mercury from produced water. The aim of this paper is to remove mercury from produced water using subcritical water assisted ionic liquid (IL) for the first time. In this study, 1-etyl-3- methylimidazolium chloride, [EMIM][Cl], IL was utilized. The potential experiments were conducted in a batch type extractor at temperatures of 130 - 180ºC, a pressure of 0.2 MPa and treatment times of 0 - 10 min. The concentration of mercury(II)ions in ILs were analyzed using UV-VIS spectrophotometer and IL was analyzed using FT-IR to study the structure of ILs. The results show that [EMIM][Cl] IL has the ability to absorb mercury from produced water and almost 99.5% mercury was removed at a temperature of 180oC, a pressure of 0.2 MPa and a treatment time of 10 min by the action subcritical water assisted [EMIM][Cl]. In addition, mercury removal follows first order kinetics with an activation energy of 2.52 kcal per mol and a pre-exponential factor of 1.093 s-1. Therefore, the subcritical water assisted ILs can be used to remove mercury from produced water of oil and gas industries.Journal of Chemical Engineering, Vol. 30, No. 1, 2017: 12-15